Analyzing Consumer Preferences for Point Coffee Beverage Attributes Through Conjoint Analysis in Surabaya - ELISTIYA NURAINI PUTRI HENDRAWAN; RATNA YULISTIANI; HADI MUNARKO (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study aimed to analyze consumer preferences toward product attributes of Point Coffee beverages at Indomaret outlets in Surabaya using conjoint analysis. The research employed a survey method with 100 respondents selected through non-probability sampling. The attributes examined included coffee menu variants, cup size, serving style, sweetness level, and service method. Conjoint analysis was applied to determine the relative importance and utility values of each attribute. The results showed that the coffee menu variant was the most important attribute (37.95%), followed by serving style (26.31%), sweetness level (13.01%), service method (11.94%), and cup size (10.80%). The highest utility values were found for Latte flavor, less ice serving, dine-in service, up-size cup, and less sugar level. These findings indicate that menu variety and serving preference significantly influence purchasing decisions. The model demonstrated good predictive accuracy (p = 0.000), confirming the reliability of the conjoint analysis in explaining consumer preferences. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 17: Partnerships for the Goals